Asbestosis: un riesgo no siempre visible que amenaza a los trabajadores de la construcción. - Anaya-Aguilar, Carmen; Torrecilla-García, Juan Antonio; Rubio-Romero, Juan Carlos; Anaya-Aguilar, Rosa María (My University, 2023)
If we propose a new approach to organisations synthesised in the "Management of Happiness" that seeks human talent so that companies can improve their competitiveness, productivity and profitability, we cannot leave aside one of the great threats that looms over workers and that affects happiness at work and, in short, organisational management, such as the issue addressed in this communication, which is the great threat posed by the indiscriminate use of asbestos in our societies. Asbestos is a carcinogenic element recognised as such by the International Office of Cancer and although it is banned in many countries such as the European Union, there are many others where it is still used such as China or Russia and despite this ban, its massive use since the Second World War has meant that the trace of materials with asbestos is extensive and present in many buildings forming part of pipes, water tanks, roof coverings, etc., which constitutes a major problem of environmental pollution and public health which can be affected especially workers in the construction sector. Therefore, the aim of this work was to see from a practical point of view the difficulty of managing the prevention of occupational risks due to asbestosis in the workers of Micro-SMEs and Self-Employed Workers in the Construction Sector. The study was carried out using the Expert Panel technique with a total of 10 professionals with extensive experience in the Construction Sector and Occupational Risk Prevention.The experts concluded that the greatest difficulty in carrying out an adequate Asbestosis Prevention Management of the group studied was the hidden asbestos as there is no census of affected buildings and constructions and the lack of awareness in a disease with a latency period of between 35-40 years where the cause-effect relationship is not so evident
Keywords: Higiene industrial; Trabajadores de la construcción - Salud e higiene; Construcción - Personal - Salud e higiene; Asbestosis; Obra menor; Obra de reforma; Micropyme; Autónomo